THE EFFECT OF DIET THERAPY ON CLINICAL AND LABORATORY PARAMETERS IN CHRONIC HEPATITIS B (World Conference on Social Sciences, Law and Public Policy, 2026)
Chronic hepatitis B (CHB) remains a significant epidemiological and clinical challenge in global healthcare. According to the World Health Organization, more than 250 million people worldwide live with this infection, and approximately 800,000 deaths annually are associated with liver cirrhosis and hepatocellular carcinoma.